Risk management in the banking sphere (Economics and region, 2024)
Risk management is a key function in banking, as banks are constantly faced with a variety of threats that can affect their financial stability and reputation. The article, based on the analysis of domestic literature, singles out the features and state of banking risk management in modern conditions. The essence of the main types of risks, according to the classification established by the National Bank of Ukraine, faced by banks, including credit risk, liquidity risk, interest rate risk, market risk, currency risk, operational and technological risk, reputational risk, legal and strategic risks, is considered. Methods of managing each of these risks are described. A comprehensive approach to bank risk management based on 5 stages has been formed, which includes: risk identification, assessment, risk management, monitoring and control, as well as the use of modern technologies for risk management. Special attention is paid to the analysis of changes in the number and structure of participants in the banking market of Ukraine during the last 10 years, which took place under the influence of economic and political upheavals. This made it possible to establish that changes in the number and composition of banking institutions testify to the constant influence of economic and political events on the banking sector of Ukraine. Each stage of development was accompanied by its own challenges that increased risks, and banks had to effectively manage them in order to maintain financial stability in difficult economic conditions. The dynamics of assets and capital of banks in Ukraine during 2014-2024 were studied, which showed a positive growth trend despite a number of risks that were exacerbated by various challenges. An analysis of the NPL level in 2018-2024 was conducted by group, as an important indicator of credit risk. The increase in the share of NPLs during the war shows the need for enhanced management of banks' credit risk. The credit risk norms of the banking system during 2019-2024 were analyzed, which showed compliance with the normative values. This shows that the banking system of Ukraine is gradually strengthening, reducing credit risks and increasing its ability to withstand external challenges. An analysis of the financial indicators of the banking system of Ukraine during 2014-2024 was carried out as an important factor influencing reputational risk. Thus, losses in 2014-2017 were due to credit risk and liquidity problems due to volatility. Later, thanks to improved economics and risk management, the banking system began to make a profit. Even in 2022-2023, during the war, banks remained profitable, which shows their ability to adapt to crises and different types of risks.
Keywords: banking system; risk management; credit risk; liquidity; war; stability; financial performance